Podcast como alternativa didática para o ensino de física no ensino médio - MOTA, Moisés Silva (2019)
Podcast is a public issue downloaded on demand, thereby obtaining information in audio format, which brings meaningful content to the recipient. It also has innovative features in the communication process that uses new technologies. Based on teaching, it presents itself as a media process that emerges from the production of audio files, a combination of audio, images and videos. This tool together with the broadcasting came to challenge our thinking about social communication and teaching, providing dynamic situations of teaching learning in a relationship between technological resources and physical principles as allies, involving participation, interest, perception and curiosity about the contents addressed. Thus, the objective of this dissertation is to present the podcast as an alternative methodological resource for the teaching of Physics in High School. In this sense, the process of production, evaluation and research of students' learning was highlighted as the theoretical basis for several authors, highlighting Moreira, 2014, and Valente, 1999, several publication articles and sites related to the topic of podcast, which we use as a technique and research procedure podcast production, especially audio formats in MP3 format, using ICT (Information and Communication Technology) in a scripted and diagnosed way. The research results point out that this tool acts in a very relevant way in the evolution of student learning and also teachers, demonstrating the action of managing the teaching-learning process and the most constructive and solid knowledge. Thus, this work proved to be potentially significant for these students by providing a more dynamic relationship between the educational technological evolution processes for an active and meaningful learning in the understanding of Newton's laws and their everyday applications, reaching the intended direction in the analysis of the educational product of the items placed and adapted, reaching varying degrees of perception and commitment of teaching learning both by the students and the teacher.